Complete remission in refractory acute lymphoblastic leukemia using blinatumomab after failure of response to CD‐19 chimeric antigen receptor T‐cell therapy. Issue 9 (28th May 2020) - Tambaro, Francesco Paolo; Khazal, Sajad; Nunez, Cesar; Ragoonanan, Dristhi; Tewari, Priti; Petropoulos, Demetrios; Kebriaei, Partow; Wierda, William George; Mahadeo, Kris Michael
Abstract: The T‐cell engager monoclonal antibody, blinatumomab, is a potential therapeutic strategy for refractory B acute lymphoblastic leukemia after failure of CD 19 chimeric antigen receptor T‐cell therapy. Abstract : The T‐cell engager monoclonal antibody, blinatumomab, is a potential therapeutic strategy for refractory B acute lymphoblastic leukemia after failure of CD 19 chimeric antigen receptor T‐cell therapy.